2017
DOI: 10.3892/mco.2017.1287
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PC3 human prostate cancer cell proliferation, invasion and migration by eicosapentaenoic acid and docosahexaenoic acid

Abstract: Abstract. The n-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), found in fish oil, exert a number of beneficial effects, and they are used in the treatment of hyperlipidemia. In recent years, EPA and DHA have been found to affect cancer cell proliferation. In the present study, PC3 cells, which are androgen-independent prostate cancer cells that resemble castration-resistant prostate cancer cells, were used to investigate a possible novel treatment for castration-resistant prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…An animal study showed that mimicking MYC overexpression induces PCa progression in PCa-model mice fed a diet high in saturated fatty acids [37]. However, suppression of PCa cell proliferation by intake of unsaturated fatty acids, such as eicosapentaenoic acids, docosahexaenoic acids, and α-linolenic acids, was demonstrated in an animal study and several in vitro experiments using human PCa cell lines [38][39][40][41].…”
Section: Fatmentioning
confidence: 99%
“…An animal study showed that mimicking MYC overexpression induces PCa progression in PCa-model mice fed a diet high in saturated fatty acids [37]. However, suppression of PCa cell proliferation by intake of unsaturated fatty acids, such as eicosapentaenoic acids, docosahexaenoic acids, and α-linolenic acids, was demonstrated in an animal study and several in vitro experiments using human PCa cell lines [38][39][40][41].…”
Section: Fatmentioning
confidence: 99%
“…A high-fat diet induces, in fact, lipid accumulation in PCa and promotes metastasis via abnormal sterol regulatory element-binding protein (SREBP)-dependent lipid metabolism [115]. Several epidemiological studies suggest that an increased intake of saturated fatty acids and a sedentary lifestyle decreases the survival rate of PCa patients, whilst unsaturated fatty acids and physical activity reduce the risk of PCa [116,117]. In recent years, n-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), present in fish oil, have been found to influence cancer cell proliferation.…”
Section: Unsaturated Fatty Acidsmentioning
confidence: 99%
“…The invasion assay was performed in transwell assay chambers with 8-μm pore size (Corning Inc., Corning, NY, USA) and ECM (Sigma Aldrich, Singapore) coating as previously described [ 17 ]. A549 and H1299 cells were added separately at a density of 5 × 10 4 cells in the upper chamber of each transwell together with 20 µg normoxia or hypoxia-derived A549 EVs in serum-free DMEM.…”
Section: Methodsmentioning
confidence: 99%